Lokpan Kuma: A Linguistic and Cultural Landscape of the Yakurr People in Southern Nigeria - Okon, Ebri (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2025)
In ancient times, before radio, television, and telephone lines, traditional communication methods facilitated information transmission and social cohesion in Africa. This study documents the cultural landscape of communication among the Yakurr People in Southern Nigeria, focusing on the Lokpan Kuma (wooden slit drum). Using a hermeneutic phenomenological approach, data was collected through focus group discussions, participant observations, video recordings, and photographs. Content analysis revealed the significance of the Lokpan Kuma in Yakurr culture. Trained initiates play the Lokpan Kuma to alert the locals of potential threats, celebrate bravery, and announce the passing of community leaders. This study contributes to ’ ’preserving the Yakurr People’s cultural heritage, promoting cross-cultural understanding, and providing insights into traditional communication systems. The findings can be integrated into culturally sensitive developments and spatial planning of rural communities to preserve the distinctive, intangible cultural heritage of the People in the face of modernization.